Assessments of risky driving: A Go/No-Go simulator driving task to evaluate risky decision-making and associated behavioral patterns. (January 2016) - Ba, Yutao; Zhang, Wei; Salvendy, Gavriel; Cheng, Andy S.K.; Ventsislavova, Petya
Abstract: This study sought to develop and validate a Go/No-Go Simulator Driving Task (G/NG-SDT) to evaluate driver risky decision-making and associated behavioral assessments at a situation-specific level. Eighty-four participants were instructed to complete a route in as short time as possible, but avoiding any violations or crashes. To achieve this aim, they had to decide to go or wait in the dilemma scenes, paired with the baseline scenes in several scenarios. High-risk drivers with more Go decisions demonstrated more violations, in both simulator tasks and real road driving, as well as higher scores of Driving Behavior Questionnaire (DBQ) violations and more Balloon Analogue Risk Task (BART) pumps. These high-risk drivers also showed distinguishable behavioral patterns in simulator driving, moderated by the specific driving situations (e.g. scenario and scene). Several behavior assessments were consistently distinguishable in all tested situations, qualified as robust indictors to predict risk-taking in more general driving situations. Highlights: High-risk and low-risk drivers in G/NG-SDT were characterized by the number of Go decisions. High-risk drivers showed more violations, as well as higher DBQ-violations scores, and more BART pumps. High-risk drivers demonstrated smaller safety margins, and more reckless longitudinal and lateral controls. Velocity, accelerator and rotation were consistently distinguishable between high and low risk drivers in all situations.